University students’ perceptions on developing constructivist learning approach in classroom settings - Doan, Cuc Thi; Vu, Tuan Van; Nguyen, Ai Nhan (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study investigated tertiary students’ perceptions regarding constructivist learning in the context of higher education in Vietnam. It aimed to examine the general perceptions of university students towards constructivist learning and the effects of constructivist learning on students’ learning outcomes. It also examined the conditions that make students more likely to embrace or resist these approaches. The study evaluated the engagement of students in problem-solving activities through the use of constructivist learning methods. A mixed-methods approach was employed, combining both quantitative and qualitative data. Specifically, the study involved a survey of 384 students from Hanoi Law University, using a researcher-made Likert-scale questionnaire and semi-structured interviews of 20 students from the sample. While descriptive and inferential statistics were used to analyze the quantitative data, the qualitative data were thematically analyzed for common themes and patterns. The results indicate that although the participants acknowledge the benefits of constructivist methods, particularly in fostering critical thinking and problem-solving, there is still uncertainty about their ability to engage in a self-directed learning approach. The findings suggest that while the constructivist approach has been recognized, practical efforts have not been made in teaching practices, teacher training, and assessment methods to create an interactive, student-centered learning environment in Vietnam.